Smart Homes, Safety, Autonomy, and Privacy in Ageing in Place - Ge Lin; Syarmila Hany Binti Haron (International Journal of Reliable and Quality E-Healthcare, 2026)
Smart home technologies are increasingly used to support aging in place, yet safety, autonomy, and privacy are often examined separately. This scoping review mapped smart-home functions and analyzed how these values interact in later-life domestic settings. Guided by the Preferred Reporting Items for Systematic Reviews and Meta Analyses for Scoping Reviews and the Sample, Phenomenon of Interest, Design, Evaluation, and Research type framework, seven databases were searched for English-language, full-length, peer-reviewed articles published from January 2000 to 23 May 2026. The final value-oriented corpus included 218 sources. Eleven functional categories were identified, with caregiver support and remote care, fall detection and prevention, social connection, cognitive support, and mobility assistance being the most prominent. The synthesis identified three recurrent mechanisms: surveillance intensification, control displacement, and redistribution of authority and responsibility. The findings indicated that smart-home adaptation requires proportionate monitoring, negotiable user control, and periodic recalibration of permissions, care roles, and accountability.